ANALISIS KETERAMPILAN MENULIS SISWA KELAS III DI SEKOLAH DASAR - Nurfauziah, Meilia; Koswara Adiredja, Rajji; Asri Pujiasti, Dea (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing skills are one of the essential language skills in elementary education as they play a significant role in developing students' communication, critical thinking, and creativity. This study aims to analyze the writing skills of third-grade students at elementary school, which include aspects of content organization, writing conventions, and handwriting neatness, as well as to identify the internal and external factors influencing these skills. This research employed a quantitative approach using a survey method. The population consisted of all third-grade students at elementary school, totaling 30 students, using a saturated sampling technique. The research instruments included questionnaires and interviews. The results showed that most students' writing skills were in the moderate category (93.3%), while both high and low categories were 3.3% each. These findings indicate that students' writing abilities are relatively stable but still require improvement through more varied teaching strategies and a supportive learning environment.